2019
DOI: 10.1039/c9cp02160d
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free SERS substrate based on rGO–TiO2–Fe3O4 nanohybrid: contribution from interfacial charge transfer and magnetic controllability

Abstract: We proposed a new ternary nanohybrid rGO–TiO2–Fe3O4 as a magnetically controllable, ultra-sensitive SERS substrate with ultra-high SERS activity and applicability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 40 publications
3
9
0
Order By: Relevance
“…An electronic flow process from the oxygen vacancyassociated electronic states of plasmonic mag-MoO 3 NCs 40,41 to the 4-MBA chemisorbed on the SLGO, as the bridge, can drive the SERS enhancements of 4-MBA. 42,43 This effect is similar to that in previous reports, where the Raman signals of 4-MBA-conjugated graphene oxide were significantly enhanced in the presence of the plasmonic semiconductor TiO 2 . 42,43 In another instance, the chemical properties of TiO 2 were employed to mediate the charge transfer between plasmonic Au or Ag and 4-MBA adsorbed onto TiO 2 .…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…An electronic flow process from the oxygen vacancyassociated electronic states of plasmonic mag-MoO 3 NCs 40,41 to the 4-MBA chemisorbed on the SLGO, as the bridge, can drive the SERS enhancements of 4-MBA. 42,43 This effect is similar to that in previous reports, where the Raman signals of 4-MBA-conjugated graphene oxide were significantly enhanced in the presence of the plasmonic semiconductor TiO 2 . 42,43 In another instance, the chemical properties of TiO 2 were employed to mediate the charge transfer between plasmonic Au or Ag and 4-MBA adsorbed onto TiO 2 .…”
Section: Resultssupporting
confidence: 90%
“…42,43 This effect is similar to that in previous reports, where the Raman signals of 4-MBA-conjugated graphene oxide were significantly enhanced in the presence of the plasmonic semiconductor TiO 2 . 42,43 In another instance, the chemical properties of TiO 2 were employed to mediate the charge transfer between plasmonic Au or Ag and 4-MBA adsorbed onto TiO 2 . 44 The rhodamine 6G/graphene platform has also been reported to encounter similar G-SERS enhancement in the presence of Au NPs.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…246 Amongst these materials, enhancing substrates based on semiconductors, such as ZnO, TiO 2 , and MoS 2 , stand out particularly since they are not only potentially cheap and stable alternatives to Ag and Au but are also photocatalytically active which allows for the construction of reusable substrates. [247][248][249][250] For example, in a proof-of-concept demonstration, Liu, Gao, et al designed photocatalytically active ternary ZnO/ZnS/MoS 2 nanocomposites, as shown in Figure 17D, which could be used as reusable substrates for SERS. 251 The nanocomposites were synthesized through in-situ chemical growth using phosphomolybdic acid hydrate (PMo 12 )@zeolitic imidazolate frameworks-8 (ZIF-8) as the precursor.…”
Section: Photocatalytic Regenerationmentioning
confidence: 99%
“…Considering that most previous studies are concerned with the detection of fluorescent dye molecules, one of the most significant challenges in this area is bringing semiconductor-based SERS to fruition in practical usage scenarios, which is vital to improving the competitiveness of the technology. This field has recently undergone rapid growth that some new applications, such as photoelectric characterization, redox biochemistry, small-ion sensing, and determination and detoxification of organic pollutants have arisen. However, significant challenges still remain for the analytical applications of semiconductor-based SERS in many practical systems, due to the complicated chemical components and difficulties in achieving highly efficient CT in relevant systems.…”
Section: Introductionmentioning
confidence: 99%